NUMERICAL STUDY OF HEAT TRANSFER ENHANCEMENT BY INSERTING DIFFERENT SIZE BALLS INSIDE TUBE - Haider L. Aneed (Mustansiriyah University/College of Engineering, 2021)
In this paper, the challenge is to increasing of the heat exchanger performance by placing different size balls inside the tubes. the development of previous studies to enhance relatively bad case of heat transfer where the inserting (a large ball and then a small ball) to collide the water molecules in the ball and generate turbulent flow (Reynolds number range from 50,000 to 350,000) and thus increase the thermal performance due to collision of particles with the inner casing of the tube and reduce the stagnation near the wall. The usefulness of small ball, after the big ball, is Reduce of gets wake flow. A simulation was made when changing the diameter ratio of big to small ball (Dr = 3, 4, 5). Also, the distance between the big ball and the small ball was changed (X = 2, 3, 5) mm. It was concluded that the best ball diameter ratio and best Distance is (Dr= D_b/D_sb = 5), (X = 3 mm), respectively. The pressure drop acts as a side effect of enhancement. Therefore, the method of equal pumping was adopted. The average thermal performance factor (TPF=1.178) of tube with insert the balls enhanced by 17.8% at (x=3mm) and (Dr=5) when compared with smooth tube.